PEMBAHARUAN DALAM SISTEM PENDIDIKAN ISLAM - Ghoni, Abdul (Jurnal al Hikmah, 2017)
Although the practice of Islamic education in Indonesia has lasted long, precisely since Islam entered the territory of the archipelago 15 centuries ago, the study of Islamic education in Indonesia is still very limited. This paper will raise about the renewal in the Islamic education system with a focal point for disclosing and answering, firstly, what is the connection between Islamic renewal and education. Second, how the education system and its components work. Third, what aspects should be updated. The study was conducted by exploring theoretically with regards to reform in the Islamic education system.